AN ASSESSMENT OF CAUSES AND EFFECTS OF MATHEMATICS ANXIETY AMONG STUDENTS OF PUBLIC SECONDARY SCHOOLS IN UYO LOCAL GOVERNMENT AREA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The study made an assessment of causes and effects of mathematics   anxiety among students of public secondary schools in uyo local government area. In order to carry out this study, specified research objectives were drawn from which research questions were formulated and used for the study. The research design for this study is a survey design. The population of the study consisted of 9473 JSS students from Uyo local government area. Simple random sampling technique was used to select 313 respondents out of the population. The instrument used for data collection was questionnaire. The instrument was validated by two experts. Data from completed questionnaires was subjected to descriptive analysis. The findings showed that causes and effects of mathematics   anxiety among students of public secondary schools in uyo local government area is statistically positive. The study recommended that The ministry of education should employ quality and skillful mathematics teachers to help bring down the level of mathematic anxiety among students of public secondary schools. The government should ensure that mathematics anxiety is assessed and addressed for students as well as teachers. The school authority should be encouraged to test students’ anxiety level and those who are found to have mathematics anxiety should be made to attend workshops or conferences specially designed to help reduce if not completely eliminate mathematics anxiety. Principals of schools should organize seminars, workshops and encourage them to attend conferences in mathematics regularly. This would build up their capacity as well as expose them to new methods of teaching mathematics in order to improve students’ performance in the subject.